Mussel-inspired nanoparticle composite hydrogels for hemostasis and wound healing - Cui, Guihua; Guo, Xiaoyu; Su, Ping; Zhang, Tianshuo; Guan, Jiao; Wang, Chungang (Frontiers in Chemistry, 2023)
Uncontrolled hemorrhage can easily lead to death from trauma. The efficient and safe hemostatic material is an urgent and increasing need for hemostatic research. Following a trauma, the wound-healing was induce by various cellular mechanisms and proteins. Hemostatic biomaterials that can not only halt bleeding quickly but also provide an environment to promote wound healing have been the focus of research in recent years. Mussel-inspired nanoparticles composite hydrogels have been propelling development for hemostatic materials owing to their unique advantages on adhesion, hemostasis and bacteriostasis. This review summarizes the hemostatic and antimicrobial fundamentals of polydopamine(PDA)-based nanomaterials and emphasizes the current developments regarding hemorrhage-related PDA nanomaterials. Moreover, the safety concerns and clinical application problems of PDA hemostatic nanomaterials were briefly discussed in this review.